Religious Moderation in Realizing Islam Rahmatan Lil Alamin - Syafi’i; Lazuardi Ramadhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Religious moderation is an approach in understanding and practicing religious teachings in a balanced, non-extreme and open manner to differences. In the midst of cultural, ethnic and religious diversity in Indonesia, religious moderation is the key to realizing Islam as a religion of mercy for all nature. This concept emphasizes Islam as a religion that brings peace, compassion and prosperity to all creatures, without distinguishing between religious backgrounds or beliefs. Religious moderation includes values such as tasamuh, justice, balance, and respect for diversity, which, if implemented well, can become the basis for creating a harmonious and inclusive social life. The implementation of religious moderation faces challenges, especially from views or groups that are more inclined towards extremist or radical thinking. However, with good education, especially through religious institutions such as the Ta'lim Council, messages of moderation can be socialized to the community. In this context, the Ta'lim Council acts as an educational medium that teaches inclusive understanding of religion, encourages dialogue between communities, and fosters a tolerant attitude among its congregation. This research aims to explore the role of religious moderation in creating Islam as a blessing for the universe, identify challenges in its implementation, and formulate effective strategies that can be implemented by religious institutions in internalizing moderation values. With religious moderation, Islam can appear as a teaching that brings goodness to all mankind and supports harmony in diverse societies.